(untitled) (Chicago, 1995)
The realities of Japanese-U.S. trade and investment relations are clouded by mistrust, misinformation, and myth. In what way is the Japanese economic system different, and is it to be emulated or challenged? The contributors, from both the United States and Japan, explore Japanese trade patterns, market structure and trade, financial markets, and industrial and trade policy. Offering analysis of the issues, Trade with Japan is a valuable resource for economists, policymakers, and the business community
Keywords: United States,Hoa Kỳ,Japan,Nhật Bản; Commerce,Thương mại,Commerce,Thương mại; Japan,Nhật Bản,United States,Hoa Kỳ